2015
DOI: 10.1016/j.bbmt.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Induction Therapy with Bortezomib Followed by Bortezomib-High Dose Melphalan and Stem Cell Transplantation for Light Chain Amyloidosis: Results of a Prospective Clinical Trial

Abstract: The depth of hematologic response has been shown to correlate with survival and organ responses for patients with light chain (AL) amyloidosis. We conducted a prospective trial of 2 cycles of induction with bortezomib and dexamethasone on a twice a week schedule followed by conditioning with bortezomib and high-dose melphalan (HDM) and autologous stem cell transplantation (SCT). The objectives were hematologic responses, tolerability, and survival. Thirty-five patients were enrolled from 2010 to 2013. Of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 39 publications
0
46
0
7
Order By: Relevance
“…These series have generally yielded favorable results in the setting of planned induction prior to transplant, in patients deemed ineligible for transplant, and in relapsed disease. 10,13,[23][24][25][26][27][28] Additionally, several comparative studies have also reported favorable outcomes with bortezomib-based induction. A 2014 matched case-control study of 174 newly diagnosed patients (many with advanced cardiac involvement) comparing frontline bortezomib/melphalan/dexamethasone (BMDex) with melphalan/dexamethasone (MDex) showed higher rate of CR with BMDex.…”
Section: Discussionmentioning
confidence: 99%
“…These series have generally yielded favorable results in the setting of planned induction prior to transplant, in patients deemed ineligible for transplant, and in relapsed disease. 10,13,[23][24][25][26][27][28] Additionally, several comparative studies have also reported favorable outcomes with bortezomib-based induction. A 2014 matched case-control study of 174 newly diagnosed patients (many with advanced cardiac involvement) comparing frontline bortezomib/melphalan/dexamethasone (BMDex) with melphalan/dexamethasone (MDex) showed higher rate of CR with BMDex.…”
Section: Discussionmentioning
confidence: 99%
“…41 Bortezomib and dexamethasone induction for 2 cycles followed by bortezomib-high-dose melphalan conditioning for SCT resulted in a 49% hematologic CR with renal and cardiac responses at 1 year of 35% and 57%, respectively. 42 In a small, randomized trial comparing bortezomib-dexamethasone induction for 2 cycles followed by high-dose melphalan SCT to high-dose melphalan and SCT alone, the bortezomib group achieved superior hematologic CR (67.9% vs 35.7%), as well as renal responses (65.2% vs 39.1%) and cardiac responses (67% vs 25%) at 1 year. 43 In patients ineligible for SCT treated with oral melphalan and dexamethasone, CR was achieved in 37% and cardiac and renal responses in 37% and 24%.…”
Section: -28mentioning
confidence: 99%
“…Egy prospektív vizsgálat során bortezomibbal kiegészített indukciót és konszolidációt követően ASCT-t végeztek. A betegek 100%-ában tapasztaltak hematológiai választ, ebből 63%-ban komplett remissziót, 10%-os TRM mellett [23].…”
Section: Aktuális Kezelési Lehetőségek Szemléletekunclassified